Assessment of the Macular Microvasculature in High Myopes With Swept Source Optical Coherence Tomographic Angiography - Wong, Chee-Wai; Matsumura, Saiko; Htoon, Hla Myint; Tan, Shoun; Tan, Colin S.; Ang, Marcus; Wong, Yee-Ling; Agrawal, Rupesh; Sabanayagam, Charumati; Saw, Seang-Mei (Frontiers in Medicine, 2021)
Background: The risk of pathologic myopia (PM) increases with worsening myopia and may be related to retinal microvasculature alterations. To evaluate this, we analysed the macular microvasculature of myopes with swept source-optical coherence tomographic angiography (SS-OCTA) in adolescent and young adult Singaporeans. Methods: This is a prevalent case-control study including 93 young Chinese from the Strabismus, Amblyopia and Refractive error in Singaporean children (STARS, N = 45) study and the Singapore Cohort Study of Risk Factors for Myopia (SCORM, N = 48) studies. Macular vessel density(VD) measurements were obtained from 3x3mm SS-OCTA scans and independently assessed using ImageJ. These measurements were compared between individuals with non-high myopia (non-HM, N = 40; SE>-5.0 diopter[D]) and HM (SE≤-5.0D, N = 53). Results: The mean macular VD was 40.9±0.6% and 38.2±0.5% in the non-HM and HM groups respectively (p = 0.01 adjusted for age and gender). Mean FAZ area in the superficial layer was 0.22±0.02 mm2 in the HM group, which was smaller compared to non-HM group (0.32±0.03 mm2, p = 0.04). Mean deep FAZ area was similar between the 2 groups (0.450.03mm2 and 0.480.04mm2 in the HM and non-HM groups, respectively, p = 0.70). Conclusions: VD was lower and superficial FAZ area was smaller, in adolescents and young adults with HM compared to non-HM. These findings require validation in prospective studies to assess their impact on the subsequent development of PM.